Lumpy Investments, Factor Adjustments and Productivity - Øivind A. Nilsen; Arvid Raknerud; Marina Rybalka; Terje Skjerpen (Statistics Norway, Research Department, 2005)
This paper describes firms' output and factor demand before, during and after episodes of lumpy investments using a rich employer-employee panel data set for two manufacturing industries and one service industry. We focus on the simultaneous adjustment of capital, materials, man-hours, as well as the skill composition and hourly cost of labour. The investment spikes lead to roughly proportional changes in sales, labour and materials, while capital intensity increases significantly. Capital adjustments are found to be smoother in the service industry than in the two manufacturing industries, a difference that may be related to the labour intensity in the service industry. Finally, the changes in productivity associated with episodes of investment spikes are small, indicating that productivity improvements are related to learning-by-doing rather than instantaneous technological changes through investment spikes.
Keywords: C13; C33; D21; D24; 330; Lumpy investments; Adjustment costs; Productivity; Panel data